EOLP-05. POSTMORTEM TISSUE DONATION: GIVING FAMILIES THE ABILITY TO CHOOSE. (14th November 2022) - Ramaswamy, Vijay; Lyons, Nicole; Frenkel, Elizabeth; Gerismov, Elena; Gustafson, Allen; Gustafson, Patti; McLean, Ginny; Ochasi, Aloysius; Waanders, Angela
Abstract: To our knowledge, Gift From a Child (GFAC) is the only dedicated consortium providing autopsy resources for children with brain tumors. Using the parental data and the experience of being a multi-institutional post mortem CNS tumor collection program, GFAC seeks to inform medical professionals of the need to approach families about post-mortem donation and demonstrate how barriers to donation can be overcome. Much like the one that occurred for organ donation, a cultural shift is needed with the goal to offer every family the option to donate. Collected survey data shows, 98% of families who donated were satisfied with their decision, compared to 20% of families who did not donate being satisfied with their decision. Most families want to be provided the opportunity to choose to donate, citing the desire to advance research and help future families. For families who donated, over 71% initiated the donation conversation with their clinician. Among those who did not donate, 58% reported they had not been asked. The healthcare team initiated the donation conversation only 20% of the time for both groups. Without the conversation being initiated, many families remain unaware of the necessity and impact of donation on advancing research. The timing and structure of how donation is brought up impacts if families proceed with donating, however, data shows that withholding this option is frequently more distressing for families. Parent interviews and survey data indicate the majority of families are most open to this conversation once it's evident a child will not survive and during transition to hospice care. Presentation donation as a driver for research, helping the next child, and as a key step in the family's grieving process positively correlate with a family's decision to donate.